FRENCH ENTERPRISE UNDER INFLATION: A BALANCE SHEET ANALYSIS. - Wasserman, Max J. (The Accounting Review, 1934)
Two opposing hypotheses attempt to explain the effects of inflation upon business enterprise. The first maintains that business profits by inflation due to the rise in prices which it engenders. The second affirms that inflation is a grave danger to business, gutting enterprises of their working capital. The first of these two hypotheses has recently been attacked by a number of German and French accounting theorists who have attempted to demonstrate that the standard accounting calculation of profits does not give accurate results during periods of rapidly changing prices. The second hypothesis is indeed most seductive, but, unfortunately, it has never been verified by a positive study of the facts. The object of this study is to investigate quantitatively the extent to which the one or the other of these theories found application in the French inflation of 1919-1926 and to discover the net effects of inflation upon the financial position of French enterprises. Several factors such as reconstruction, tariffs, improved industrial techniques, have all played an important part in these changes.